Playful punctuation in primary children's writing. (12th April 2022) - Burrell, Andrew; Beard, Roger
Abstract: The writing of three attainment groups of 10‐ to 11‐year‐old children was used to investigate their use of ludic (playful) punctuation in the composition of an advertisement for a new dessert. Framed within a consideration of language play in general, and children's use of punctuation in particular, the investigation revealed the ways in which primary children use playful punctuation in order to achieve their persuasive aims. There were clear differences between the attainment groups in both the content and range of these uses. The findings suggest that such uses—like language play as a whole—warrant further attention in educational research. Children use playful punctuation in distinctive ways without being prompted to do so. Future work needs to identify the writing tasks that enable the use of playful punctuation to flourish.